Taking on a New Grading System: The Interconnected Effects of Standards-Based Grading on Teaching, Learning, Assessment, and Student Behavior. (March 2019) - Knight, Megan; Cooper, Robyn
This study explored high school teachers' perceptions of the effects of standards-based grading (SBG) on planning, instruction, assessment, classroom management, and student behaviors. Findings indicated that despite some infidelity and an initial implementation dip, systemic (SBG) changes made teaching clearer, more purposeful, and more conducive to student needs while enhancing student growth mind-set and ownership. The researchers concluded SBG is a viable reform because it makes teaching and learning more focused, effective, and enjoyable. Findings also led to several recommendations for administrators and teachers.